Correlation of CD133 and SOX2 Expression with Regional Lymph Nodes Metastatic Status in Invasive Breast Carcinoma of No Special Type - Dyah Fauziah; Sutrisno Sutrisno; Gondo Mastutik (Indonesian Journal of Cancer, 2021)
Background: CD133 overexpression can increase cell proliferation, migration, and epithelialmesenchymal transition that promotes metastasis. CD133 expression is induced by hypoxiainduced factor (HIF) which requires SOX2 binding in the promoter region. SOX2 is an embryonal transcription factor that plays a role in the development of malignancy. The study aimed to analyze the expression of CD133 and SOX2 with regional lymph nodes (LN) metastatic status in invasive breast carcinoma of no special type (NST). Methods: The study was a cross-sectional design. Forty-five samples were retrieved from pathology archives in Dr. Soetomo Hospital from January to December 2018. Samples were divided into 2 groups, with and without regional LN metastasis. Immunohistochemistry with CD133 and SOX2 was applied to all samples. CD133 expression was assessed by immunoreactive score, and SOX2 expression was assessed by the percentage of tumor positive cells.Results: There was no significant difference in CD 133 expression between invasive breast carcinoma of NST with and without regional LN metastases (P = .990). A positive correlation was found in SOX2 expression between breast carcinoma with and without regional LN metastasis (P = .000; rs = .518). There was no correlation between CD133 and SOX2 expression (P = .082), which means that the high expression of CD133 did not affect SOX2 expression.Conclusions: CD133 expression was not significantly different in breast carcinoma with and without LN metastasis. The high expression of SOX2 was found significantly correlated with regional LN metastasis. SOX2 expression may become a potential prognostic marker in invasive breast carcinoma of NST. regional LN metastasis